TComparison of Croatian Foreign Language Teachers' General Propensity towards the Use of ICT and Its Impact on the Foreign Language Teaching Process - Krunoslav Mikulan; Vladimir Legac; Predrag Oreski (Athens Institute for Education and Research, 2017)
In this paper the authors present some of the results of a research into the influence of information and communication technologies (ICT) on foreign language (FL) teaching. The survey was conducted on a sample of 255 FL teachers (N= 255) in the Republic of Croatia. The teachers are eployed at primary and secondary schools, or at universities, and they teach six different FLs. The vast majority possess a PC at home and/or work, and have access to the Internet, but less than half teach FLs in classrooms equipped with a computer. The starting hypothesis was that the increase of the time teachers spend on their computers and the Internet would lead to the increase in their ICT competences. The results of the study have confirmed the authors' hypothesis: Correlation quotients have shown that there is a positive statistically significant correlation between the amounts of time spent using ICT and the attitudes of FL teachers regarding their own assessment of competence for the successful application of ICT in the FLs teaching. The analysis of the results presented in the paper mainly focus on correlations between the amount of time spent using ICT and the teachers' self-assessments of their 12 different computer competences and the evaluation of their experience with ICT equipment and software.